A Frameshift Mutation in the Cubilin Gene (CUBN) in Border Collies with Imerslund-Gräsbeck Syndrome (Selective Cobalamin Malabsorption) - Owczarek-Lipska, Marta (Public Library of Science, 2013)
Imerslund-Gräsbeck syndrome (IGS) or selective cobalamin malabsorption has been described in humans and dogs. IGS occurs in Border Collies and is inherited as a monogenic autosomal recessive trait in this breed. Using 7 IGS cases and 7 non-affected controls we mapped the causative mutation by genome-wide association and homozygosity mapping to a 3.53 Mb interval on chromosome 2. We re-sequenced the genome of one affected dog at ∼10× coverage and detected 17 non-synonymous variants in the critical interval. Two of these non-synonymous variants were in the cubilin gene (CUBN), which is known to play an essential role in cobalamin uptake from the ileum. We tested these two CUBN variants for association with IGS in larger cohorts of dogs and found that only one of them was perfectly associated with the phenotype. This variant, a single base pair deletion (c.8392delC), is predicted to cause a frameshift and premature stop codon in the CUBN gene. The resulting mutant open reading frame is 821 codons shorter than the wildtype open reading frame (p.Q2798Rfs*3). Interestingly, we observed an additional nonsense mutation in the MRC1 gene encoding the mannose receptor, C type 1, which was in perfect linkage disequilibrium with the CUBN frameshift mutation. Based on our genetic data and the known role of CUBN for cobalamin uptake we conclude that the identified CUBN frameshift mutation is most likely causative for IGS in Border Collies.